Creation of Materials from Tabular BRDFs - Nunes, Mislene da Silva; Miranda Jr., Gastão Florêncio; Andrade, Beatriz Trinchão (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2022: Anais Estendidos da XXXV Conference on Graphics, Patterns and ImagesDO - 10.5753/sibgrapi.est.2022.23257, 2022)
Rendering materials with a realistic appearance requires considering how they interact with the light. Bidirectional Reflectance Distribution Functions (BRDFs) are often used to achieve this goal. There are different ways to represent materials from BRDFs, which include tabular BRDFs, analytical models, and linear combinations of a BRDF database. In the last decade, the search for more realism in rendering increased the interest in using tabular BRDFs. However, this approach requires a long acquisition process and high storage space. This master dissertation proposes a pipeline to create new materials from a tabular BRDF database. During this process, we also explored two related topics: we compiled and proposed techniques to evaluate BRDFs, and developed an approach to preprocess and cluster a BRDF database. These researches presented insights and contributions that are useful for contexts other than ours and provided analysis that reinforced our choice of techniques to reach our goal. As a final result, our method creates new materials with realism and consistency.